Review on the therapeutic activities of the genus Trichilia (Research, Society and Development, 2021)
The genus Trichilia (Meliaceae family) has been attracting interest among Brazilian Flora, due to the biological activities of its secondary metabolites. This genus has species distributed throughout tropical America, recognized for its significant economic importance and high commercial value. Its composition consists mainly of terpenoids (triterpenes, sesquiterpenes, limonoids and steroids) and polyphenols (flavonoids and tannins). In folk medicine this genus is used in preparations such as antimicrobial, antimalarial, antiviral and antioxidant. Studies carried out with several species of the genus Trichilia show that these plants have antioxidant, anticholinesterase, antimicrobial activities against pathogens of great clinical importance, neuroprotective, anti-anaphylactic and anti-inflammatory. In addition, analgesic, antineoplasic, hepatoprotective and immunomodulatory activities have also been investigated and proven in the literature. Based on the great biotechnological potential of the genus Trichilia, from the few studies on its applications in human health and in view of the importance of searching for natural substances that have effective therapeutic activities, this review highlights the main therapeutic applications of species of this genus found in the literature, and stimulate further studies on the use of these plants in the treatment of various diseases. For this, a survey on the topic was carried out in the main sources of scientific research in the period from 2005 to 2020, leading us to conclude that this genus can be a potent ally in the search for new phytotherapic drugs.